The Effect of Work Stress on Turnover Intention Through Job Burnout at Prof. Dr. R. D. Kandou Manado Hospital - Arianto, Eko (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
Using the survey method, this quantitative research aims to examine the effect of work stress on turnover intention, with job burnout as a mediating variable among medical personnel at the Central General Hospital, Prof. R. D. Kandou, Manado. Through random sampling techniques, as many as 105 respondents out of 120 medical personnel were selected as samples, and data was obtained using a closed questionnaire. Data analysis was carried out using the SEM-PLS (Structural Equation Modeling-Partial Least Squares) method using SmartPLS 3 software to evaluate the validity and reliability of indicators and test the relationship between variables in the research model. This study found that work stress had a positive and significant effect on job burnout, with an influence value of 0.794, and turnover intention, with an influence value of 0.455. At the same time, job burnout positively affected turnover intention, with an influence value of 0.433. It is proven that the higher the level of work stress in medical personnel, the more likely they are to experience burnout and intend to leave work.